Photocell modernization - Iskakov, Bakhtiyar; Altayqyzy, Marzhan; Tautayev, Yernar; Ongarova, Shynar; Karmenov, Kanat (The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems; Nazarbayev University; National Laboratory Astana; Institute of Batteries, 2020)
In our modern world, where science is developing rapidly, it is difficult to determine a specific area of science, which is more promising than the rest. One of the promising areas of science is research aimed at obtaining cheap energy. In the near future, all world reserves of combustible fuel will end: coal, oil, etc., so it remains to develop and study renewable energy sources, such as wind energy, hydropower, solar energy, bioenergy, geothermal energy and, of course, nuclear power. Out of competition, of course, is nuclear power. Despite this, I propose to consider the issue of solar energy. There are minuses and pluses of solar energy. In this article, I propose ways to solve them. The possibilities of using solar energy are limited by a very low energy density, as well as its fluctuations in time, which leads to a huge area of solar radiation collectors and a large material consumption of energy production. For example, in the winter season or at night. A photoelectric effect is the emission of electrons by a substance under the influence of light. The photoelectric effect occurs under the influence of electromagnetic radiation, and electromagnetic radiation is not only photons. Cosmic rays can become a new source for the operation of the solar cell, since they have tremendous energy. A solar cell operating under the influence of cosmic rays will work around the clock, regardless of the seasons. But the main problem is the question of how we will do it. It is known that the flux and energy of cosmic rays are colossal, from several eV to 1020 eV. It is also known that particles passing through the so-called scintillators give a flash, and our idea is to use these flashes for the operation of the photocell. This technique has not yet been studied and is not being studied by all. In the near future, people will learn this technique and we can use solar panels around the clock. The future is for high energy physics.
Keywords: photocell; solar energy; photoelectric effect; Research Subject Categories::TECHNOLOGY